2007
DOI: 10.1007/s10457-007-9054-9
|View full text |Cite
|
Sign up to set email alerts
|

Response of Sesbania sesban (L.) Merr. to rhizobial inoculation in an N-deficient soil containing low numbers of effective indigenous rhizobia

Abstract: Sesbania sesban (L.) Merr. (sesbania) is a fast growing N 2 -fixing widely used as an improved fallow species by smallholder farmers in eastern and southern Africa to restore fertility of their N-deficient soils. In order to establish the need for inoculation, the population of sesbania rhizobia in soil collected from a site where the species is intended for introduction was assessed using the most probable number (MPN) plant infection assay. The MPN of sesbania rhizobia was low (21, 6-81 fiducial limits at P=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Notwithstanding the difference in MPN estimates of indigenous rhizobia capable of nodulating S. senegal in Dahra and Goudiry soils, inoculation in most cases improved nodulation. In addition, indigenous rhizobial strains originally isolated from Goudiry generally performed better than exogenous strains in Goudiry soil despite high indigenous populations, indicating the importance of selection and re-inoculation with an effective indigenous strain as previously demonstrated in Sesbania sesban by Makatiani and Odee (2007). Besides natural adaptation, the reinoculated strain is also expected to reduce competion for nodulation from other compatible indigenous soils.…”
Section: Discussionmentioning
confidence: 65%
“…Notwithstanding the difference in MPN estimates of indigenous rhizobia capable of nodulating S. senegal in Dahra and Goudiry soils, inoculation in most cases improved nodulation. In addition, indigenous rhizobial strains originally isolated from Goudiry generally performed better than exogenous strains in Goudiry soil despite high indigenous populations, indicating the importance of selection and re-inoculation with an effective indigenous strain as previously demonstrated in Sesbania sesban by Makatiani and Odee (2007). Besides natural adaptation, the reinoculated strain is also expected to reduce competion for nodulation from other compatible indigenous soils.…”
Section: Discussionmentioning
confidence: 65%
“…Makatiani and Odee (2007) showed that it is better to inoculate with effective indigenous than exogenous rhizobia Sesbania sesban plants.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the hypothesis of this work was stated that inoculation of rhizobia isolated from native soil improves the nodulation and yield of peanut even though the soil native rhizobia population has been > 10 2 g −1 soil. Our approach has been to utilize indigenous rather than exotic rhizobia, since the former, already adapted to the existing ecological conditions, can provide very satisfactory results (Douka and Xenoulis 1987;Hungria et al 1996;Makatiani and Odee 2007). Therefore, the objective this work was to evaluate the symbiotic effectiveness of selected indigenous Bradyrhizobium sp.…”
Section: Introductionmentioning
confidence: 99%